Manual of Diagnosis and Professional Practice in Mental Retardation. 1996
DOI: 10.1037/10203-055
|View full text |Cite
|
Sign up to set email alerts
|

Counseling and psychotherapy.

Abstract: Although service providers have increasingly recognized that individuals with mental retardation (MR) may be afflicted with a wide range of psychiatric and adjustment disorders, as are individuals in the normal range of intelligence, counseling and psychotherapy are often neglected as treatment modalities because it is assumed that MR precludes effective participation in the therapeutic process. Such beliefs are unfounded, as demonstrated by numerous case reports and writings that reflect the effectiveness of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…In particular, the cognitive and psychodynamic psychotherapies have been made available (Benson et al. 1986; Beail & Warden 1996; Hurley et al. 1996; Beail 1998) along with new pharmacological approaches, such as the atypical antipsychotics (Buzan et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the cognitive and psychodynamic psychotherapies have been made available (Benson et al. 1986; Beail & Warden 1996; Hurley et al. 1996; Beail 1998) along with new pharmacological approaches, such as the atypical antipsychotics (Buzan et al.…”
Section: Introductionmentioning
confidence: 99%
“…1998). Simultaneously, calls for research to evaluate these new approaches have been issued (Nezu & Nezu 1994; Hurley et al . 1996).…”
Section: Introductionmentioning
confidence: 99%
“…These concerned individuals who appeared to be handicapped by emotional difficulties or were of low average ability rather than having a diagnosis of intellectual disability (mental retardation) (Sinason 1992). Reviews published two decades later, similarly only reported that there were a few case studies (Nezu & Nezu 1994; Hurley et al. 1996).…”
mentioning
confidence: 99%
“…Despite some evidence to the contrary (Taylor, Lindsay, & Willner, 2008), there still is an assumption amongst clinicians that people with IDs may not benefit from 'talking therapies' (Hurley, Pfadt, Tomasulo, & Gardner, 1996). These assumptions reflect the exclusion of people with IDs from theoretical developments which underpin applied psychological interventions.…”
mentioning
confidence: 99%